Enhancing Friction Stir Spot Welding of Al 5754 and Al 6111 Joints Using Taguchi’s Technique - Vikram P N Gowda; Keshavamurthy R.; Naveena B. E.; Solomon Jenoris Muthiya; Joshuva Arockia Dhanraj; Johannex Fefeh Rushman; Amit Verma (Journal of Engineering)
The present study investigates the impact of varying process parameters on the mechanical properties of friction stir spot welding (FSSW) joints involving Al 5754 and Al 6111. Taguchi’s L16 design of experiment approach was employed to conduct experiments and optimize the process parameters. Key parameters, including tool pin profile, dwell time (5–30 sec), rotating speed (250–1400 rpm), and plunge depth (1.5–1.8 mm), were systematically considered. The results indicated that the optimized welding conditions for attaining higher tensile-shear strength are a spindle speed of 1400 rpm, dwell time of 10 sec, plunge depth of 1.7 mm, and a tool pin profile of a triangular pyramid. As for bending strength, the optimal conditions are a spindle speed of 250 rpm, dwell time of 30 sec, plunge depth of 1.8 mm, and a tool pin profile of a square pyramid, representing higher bending strength. The analysis of variance technique revealed that the tool pin profile and plunge depth significantly influenced the tensile-shear strength and bending strength of the developed FSSW joint, respectively. Regression analysis was employed to formulate mathematical models predicting tensile and bending strength, and the predicted values closely matched experimental results with 80% accuracy.